The World Bank Research Observer 15(1) - World Bank (Washington, DC: World Bank, 2013)
Crisis, adjustment, and reform in Thailand's industrial firms; by David Dollar and Mary Hallward-Driemeier. Corporate performance in the East Asian financial crisis; by Stijn Claessens, Simeon Djankov, and Lixin Colin Xu. Industrial policy : growth elixir or poison?; by Howard Pack. Financial safety nets : lessons from Chile; by Philip L. Brock. Lessons in structuring derivatives exchanges; by George Tsetsekos and Panos Varangis. Growth and institutions: a review of the evidence; by Janine Aron.